2004
DOI: 10.1021/ja049876m
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Model DNA Fragments from Very Low-Energy (<1 eV) Electrons

Abstract: Although electrons having enough energy to ionize or electronically excite DNA have long been known to cause strand breaks (i.e., bond cleavages), only recently has it been suggested that even lower-energy electrons (most recently 1 eV and below) can also damage DNA. The findings of the present work suggest that, while DNA bases can attach electrons having kinetic energies in the 1 eV range and subsequently undergo phosphate-sugar O-C sigma bond cleavage, it is highly unlikely (in contrast to recent suggestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
215
2
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(230 citation statements)
references
References 9 publications
6
215
2
7
Order By: Relevance
“…The problem of photostability mainly concerns DNA directly exposed to light. Hard radiation, however, easily penetrates the body and is known to generate slow secondary electrons that can subsequently attach to DNA, leading to single-and doublestrand breaks in the double helix (37)(38)(39)(40)(41)(42). Dissociative electron attachment of low-energy electrons (Ͻ3 eV) to adenine injects an electron into an empty * orbital and leads exclusively to dehydrogenation at the N9 position (40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of photostability mainly concerns DNA directly exposed to light. Hard radiation, however, easily penetrates the body and is known to generate slow secondary electrons that can subsequently attach to DNA, leading to single-and doublestrand breaks in the double helix (37)(38)(39)(40)(41)(42). Dissociative electron attachment of low-energy electrons (Ͻ3 eV) to adenine injects an electron into an empty * orbital and leads exclusively to dehydrogenation at the N9 position (40).…”
Section: Resultsmentioning
confidence: 99%
“…This could be tested in future TPRES experiments by attaching electron-withdrawing substituents to adenine at the N9 position. Work on low-energy electron attachment suggests that electrons attach either to the phosphate P ϭ O * orbital or directly to a * orbital of the nucleobase (39,43). Theoretical considerations show that electron attachment to a * orbital at the nucleobase can lead to rupture of the COO bond between the sugar and the phosphate (39,(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation induced damage in biomolecules is currently a hot topic in molecular physics since research has shown that irradiation with particle/photon energies below the ionizing potential can induce damage in deoxyribonucleic acid (DNA) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Yet little is known about the possible outcome of damage to the base pairs in terms of energetics and possible structural changes that can lead to strand breakage and therefore loss of genetic information. Sophisticated experimental techniques have been used to investigate the causes and effects of DNA damage and also to determine structural features, as well as delving into the electron-binding ability of the bases and base pairs (1)(2)(3)(4). Some of the more advanced experimental and theoretical methods have also been applied to model systems in both the gas and liquid phases to estimate and predict the physical properties and to study hydrogen bonding in purine and pyrimidine base pairs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%